Hubungan antara dimensi adversity quotient dengan kepuasan kerja pada wirausaha wanita (studi kasus pada wirausaha fashion dan kuliner di kota samarinda) - Suryanti, Siti (JURNAL MANAJEMEN, 2016)
The purpose of this study was to determine the relationship between the dimensions of Adversity Quotient with Job Satisfaction entrepreneurs . The independent variables consist of Control , Ownership , Reach and Endurance . The dependent variable is job satisfaction entrepreneurs (Y). Samples numbered 80 entrepreneurs were taken by purposive sampling technique. The analysis is a correlation analysis using Pearson product moment with the results for each variable that the variable Control obtained the results of correlation of 0.608 with a strong interpretation and determination of the value of 36.9%, for the Ownership variables obtained correlation results amounted to 0.573 with the interpretation is quite strong and the value of determination of 32.9%, to Reach variables obtained the results of correlation of 0.621 with a strong interpretation and determination of the value of 38.5%, and for variable Endurance obtained the results of correlation of 0.539 with interpretation is quite strong and the value of determination by 29.1% while the rest influenced by other variables not included in the study. The results obtained conclusion that between adversity quotient variable dimension Control, Ownership, Reach and Endurance with an entrepreneur Job satisfaction has a positive and significant relationship.Keyword : Control , Ownership , Reach , Endurance and Job Satisfaction